Gaya Belajar Siswa Berprestasi Pada Mata Pelajaran IPS di SMP Negeri 3 Jakarta - Annisa Puji Rahayu; Dian Alfia Purwandari; Nandi Kurniawan (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
Education has a very important role in human life because it can improve or develop their knowledge and attitudes. In achieving educational goals there is one factor that is quite important, namely learning style. Each student's learning style can be different, so the researcher aims to be able to describe the learning styles of outstanding students in social studies subjects at SMP Negeri 3 Jakarta. This research uses descriptive research methods with a quantitative approach. The results obtained from this research are that students who excel in social studies subjects at SMP Negeri 3 Jakarta have diverse and even learning styles. Among the three learning styles, namely visual learning style, auditory learning style, and kinesthetic learning style, there is no learning style that is superior or more widely used by students.